Simulation of the interaction between an edge dislocation and ⟨111⟩ interstitial dislocation loops in α-iron. Issue 3 (3rd April 2019) - Grammatikopoulos, Panagiotis; Bacon, David J.; Osetsky, Yuri N.
ABSTRACT: The dependence of the interactions of intermediate-size ½<111> self-interstitial atom (SIA) loops with an edge dislocation on strain rate and temperature was investigated by molecular dynamics (MD) simulations for the interatomic potential derived by Ackland et al. (A97). For low temperatures ( T = 1 K), the mechanisms of the interactions were in agreement with recent literature. It was shown that a second passing of the dislocation through the loop led to a different mechanism than the one that occurred upon first passing. Since these mechanisms are associated with different SIA loop sizes, and since the loop lost a number of SIAs upon first interaction, it was deduced that the dividing threshold between large and small loops (rendering them strong or weak obstacles, respectively) is at the vicinity of the loop size studied (169 SIAs). For higher temperatures ( T = 300 K), the strain rate dependence proved strong: for low strain rates, the dislocation absorbed the loop as a double super-jog almost immediately and continued its glide unimpeded. For a high strain rate, the dislocation was initially pinned due to the formation of an almost sessile segment leading to high critical stress.